Analisis Risiko Penurunan Kualitas Instalasi Pengolahan Lumpur Tinja Jabon Kabupaten Sidoarjo dengan Metode Failure Mode and Effect Analysis - Nasilla Aulia Faradina; Naniek Ratni J.A.R (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
As the population grows, so does the need for proper sanitation. Domestic or sanitary wastewater is the wastewater resulting from the use of water in all human activities and is divided into grey and black water. Fecal sludge, which is included in the black water category, is a source of pollution consisting of dissolved solids with a high content of organic material and microorganisms. The initial treatment of fecal sludge is carried out in domestic septic tanks, which have certain capacity limits, so further treatment of fecal sludge is required, which is carried out at the IPLT. This research uses the Failure Mode and Effect Analysis (FMEA) method to identify potential failures in the fecal sludge processing process. The aim of the research is to identify the sources and risks of processing unit failure, which can lead to a reduction in the quality of the processing results, and to propose improvements. From the research results it was found that the causes of failure with the highest RPN values and treatment priority were detention time (dt) in collection ponds, BOD removal in anaerobic ponds and BOD removal in facultative ponds. Suggested improvements can be used as suggestions for fecal sludge treatment to improve service quality